Nigeria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper and Statistical Appendix on Nigeria reviews economic development in Nigeria during 1994-97. Economic activity in Nigeria picked up modestly from its previously low growth rates in 1996-97, as growth in real GDP averaged 4 percent, compared with an average of less than 2 percent during 1992-95. The recovery was underpinned by steady growth in the petroleum sector, which comprises more than 40 percent of GDP and which benefited from buoyant world market demand and high international prices.